Analisis Efisiensi Kinerja Water Tube Boiler Berbasis Kapasitas Olah di PKS PT Mulia Sawit Agro Lestari (MSAL) - As'ari, Farhan; Yunaidi, Yunaidi; Panjaitan, Mutiara Damanis (Perkebunan dan Lahan Tropika, 2025)
Several factors influence boiler efficiency, including boiler pressure, feedwater temperature, the amount of steam generated, fuel consumption, and the calorific value of the fuel. The objective of this final project report is to determine the relationship between boiler pressure variation and steam generation, the relationship between boiler pressure variation and boiler efficiency, the relationship between feedwater variation and boiler efficiency, the relationship between the amount of steam produced and boiler efficiency, the relationship between processing capacity and boiler efficiency, as well as to analyze the calorific value of fuel consisting of 82.6% fiber and 17.4% shell, and to evaluate overall boiler efficiency. The analysis shows that an increase in boiler pressure results in a higher amount of steam produced, although the increase is not significant. The relationship between steam enthalpy and boiler efficiency demonstrates a positive trend. For instance, when the steam enthalpy reached 669.4 Kcal/kg, the boiler efficiency was 68%, while at 669.5 Kcal/kg, the efficiency increased to 69%. This finding indicates that boiler pressure significantly affects efficiency performance, as higher pressure generally enhances boiler efficiency. Furthermore, processing capacity strongly influences boiler efficiency. A higher processing capacity leads to higher efficiency, as it increases the availability of fuel for combustion, thereby enabling more complete combustion.